A study of refurbishment of listed buildings into a new facilities - Nurfarahana, Yaacob (2010)
This research is a study on the refurbishment of old building and heritage building in Malaysia. This research intends to highlight the existing practice on rehabilitation projects in Malaysia with the main focus on guidelines at rehabilitation work stages. Besides that, this research describes building restoration and the process of the renewal and refurbishment of the fabric of a building. The objectives of doing this research are to emphasize the importance of refurbishment in order to reserve an old and historical building without make big changes at the façade and structure of the buildings. This research also important in order to study on the space utilization for internal after the buildings have been refurbished and finally to determine various of commercial building that have been refurbished for a new facilities and find the most rapidly area with the preservation and conservation of buildings. The phase covers a wide span of activities, from the cleaning of the interior or exterior of a buildings Buildings are structures which have, from time to time, particular purposes. They require ongoing maintenance to prevent them falling into disrepair as a result of the ravages of time and use. Building restoration can be thought of as that set of activities which are greater than year-to-year maintenance. This research was held at Malacca, Batu Pahat and Muar. This is because; there is many old building and historical building that constructed during the British Colonial and others. The design gave an aesthetic value to the tourist. Based on this research, Malacca is the most rapid area with a refurbishment development because Malacca was awarded with World Heritage List by UNESCO. It is important for Malacca to maintain their historic and aesthetic value of the buildings. Batu Pahat was found the slowest region in refurbishment development.